2020
DOI: 10.1177/0309364620913459
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the transfemoral prosthetic socket interface designs on skeletal motion and socket comfort

Abstract: Background: The most crucial aspect of a prosthesis is the socket, as it will directly determine gait stability and quality. The current standard of care ischial ramus containment socket is reported to increase coronal stability through gait; however, socket discomfort is the primary complaint among prosthetic users. Objectives: The purpose of this study is to compare ischial ramus containment to alternatives in the transfemoral amputee population. All subjects were fit with three different sockets: traditiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…46 Sub-ischial sockets appear to be comparable to ICS in coronal plane stability and vertical movement, but with lower peak pressure at the proximal-medial brim during gait. 24,47,48 Greater socket comfort and a narrower base-ofsupport during gait were reported for the sub-ischial socket compared to ICS due to its lower proximal trim line. 24,47 A literature review of transfemoral socket suspension systems concluded that in addition to suspension enhancement, use of liners and inner flexible socket walls improves function, and comfort, and may reduce the rate of skin problems.…”
Section: Clinical Effectiveness Researchmentioning
confidence: 99%
“…46 Sub-ischial sockets appear to be comparable to ICS in coronal plane stability and vertical movement, but with lower peak pressure at the proximal-medial brim during gait. 24,47,48 Greater socket comfort and a narrower base-ofsupport during gait were reported for the sub-ischial socket compared to ICS due to its lower proximal trim line. 24,47 A literature review of transfemoral socket suspension systems concluded that in addition to suspension enhancement, use of liners and inner flexible socket walls improves function, and comfort, and may reduce the rate of skin problems.…”
Section: Clinical Effectiveness Researchmentioning
confidence: 99%
“…11 Most published studies focus on TF amputee gait, socket design, suspension and/or function of the components including less than 15 amputees. 8,[18][19][20] Kahle et al found that different socket designs may have an effect on gait speed and risk of falling. 8 Fatone et al, have described a new interface and the fabrication methods used to produce a TF socket, including outcomes from two cases.…”
Section: Cpojmentioning
confidence: 99%
“…21,22 Kahle et al, investigated the trimline level and compared outcomes between socket designs in 15 cases, although only in a clinical setting. 18 The socket designs in these studies are mainly grounded on the prosthetist's experience, with few measurable design parameters or description of how the design is intended to affect and interact with the user's residual limb during the gait cycle. 11 Various terms have been proposed to describe the way forces are transferred between the residuum and the socket, the biomechanical principles upon which these terms are based are ill-defined.…”
Section: Cpojmentioning
confidence: 99%
“…Limb amputations cause serious physical disabilities worldwide and compromise peoples’ quality of life globally. In the USA alone, in 2005, there were an estimated 1.6 million persons living with limb loss in the United States, with 19% to 21% of those individuals living with a transfemoral (above knee) lower limb amputation [ 1 ]. These numbers could double by 2050 due to the increasing rates of vascular disease and diabetes [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%